Methods of the estimation of reliability of the software of failure-safe systems avioniks - Зеленков, О. А.; Бунчук, О. О.; Мірошниченко, О. Г. (Proceedings of National Aviation University (archive), 2003)
The paper deals with providing software reliability control for up to date on-board fault-tolerable computer-assisted management systems, created on the base of integral modular aircraft electronics technology, during operational period. The authors describe the method of software failures probability evaluation and serial calculating algorithm, based determining the margins of software failures number, according to operational control data